Teori Phonology English Vowels - T. Khoirunnisa.YL; Winda Khofifah; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2023)
The study addresses vowel phonology in English with a focus on basic concepts, phonemic analysis, change, and phonological rules. Vowel phonology involves the study of vowel sounds in language and the way they are organized and grouped in the language system. Vowel phonemic analysis identifies an inventory of vowel phonemes in English and classifies them based on differences in word meaning. The distribution of vowel phonemics and allophonies describes the mapping of vowel phonemes in a particular phonological context. Vowel phonological changes occur over time and are influenced by factors such as phonetic influences, phonological environment, and contact with other languages. The study also highlights examples of phonological changes in vowels in English, including diphthongs to monophhongs and shifts in vowel sound height. Vowel phonological rules govern the pronunciation of vowel sounds in English, including allophony rules and phonological environmental influences. An understanding of vowel phonology in English has important implications in linguistic analysis and research on the history and change of language. Keywords:, mooflog and vocal